Challenges to the Implementation of the Job Creation Law on Workers' Constitutional Rights - Suyuti, Mahmud; Hardyansah, Rommy; Darmawan, Didit; Wibowo, Agung Satryo; Khayru, Rafadi Khan (Bulletin of Science, Technology and Society, 2023)
The implementation of the Job Creation Law in Indonesia has changed the regulatory landscape regarding layoffs. This regulation brings flexibility in the labor market, but is often perceived as reducing worker protection. Using a normative juridical approach, this research explores the impact of regulatory changes on workers' rights and the challenges of implementation. Constraints such as weak legal supervision, declining role of labor unions, and uncertainty of legal procedures are highlighted. The research also suggests strategies based on “flexicurity” and social dialogue to balance the interests of companies and the rights of workers in order to create a more equitable and sustainable labor market.